A numerical study of a greenhouse CFD simulation including radiation heat transfer and transpiration. (2017) - Farber, Karin; Farber, Peter; Grabel, Jens; Krick, Sebastian; Ueberholz, Peer
Radiation and transpiration are important physical phenomena in greenhouses. In this paper, we present a 3D computational fluid dynamics (CFD) simulation of a system model of a small greenhouse to investigate heat fluxes due to radiation and transpiration. The system model of the greenhouse includes incoming radiation by the sun, radiation heat transfer exchange with the surrounding, convection heat transfer, an active ventilation, open windows, a porous media modelling tomato crop, and a transpiration model coupled to the porous medium of the tomato crop. All simulations were performed transient; modelling the global location of the city of Venlo in the Netherlands with the moving sun. The fine five million cell mesh allowed a high spatial discretisation which, together with a moderate time discretisation, showed details in transpiration and radiation absorption inside the crop as well as details of the humidity distribution inside and around the tomato crop.